2017
DOI: 10.1111/jam.13468
|View full text |Cite
|
Sign up to set email alerts
|

EnvironmentalEscherichia coli: ecology and public health implications-a review

Abstract: Summary Escherichia coli is classified as a rod‐shaped, Gram‐negative bacterium in the family Enterobacteriaceae. The bacterium mainly inhabits the lower intestinal tract of warm‐blooded animals, including humans, and is often discharged into the environment through faeces or wastewater effluent. The presence of E. coli in environmental waters has long been considered as an indicator of recent faecal pollution. However, numerous recent studies have reported that some specific strains of E. coli can survive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
387
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 612 publications
(485 citation statements)
references
References 87 publications
16
387
0
14
Order By: Relevance
“…The sample collection period spanned over the two seasons in Ghana, that is, the dry and rainy seasons. All water sampling and preservation procedures were performed according to Standard Methods for the examination of water and wastewater [16, 17] and WHO guidelines for drinking water quality [14, 15]. Sampling for bacteriological analysis was done aseptically with care, ensuring no external contamination of samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample collection period spanned over the two seasons in Ghana, that is, the dry and rainy seasons. All water sampling and preservation procedures were performed according to Standard Methods for the examination of water and wastewater [16, 17] and WHO guidelines for drinking water quality [14, 15]. Sampling for bacteriological analysis was done aseptically with care, ensuring no external contamination of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are several studies assessing multidrug resistance (MDR) in E. coli populations of animal origin, not much work has been done on the ecology of MDR [13, 14]. The spread of MDR into environments where antibiotics are not used is a possibility that has not yet been well researched, although it has been postulated that water could disseminate antimicrobial resistance [15]. The objectives of this study are to determine the antibiotic sensitivity pattern and the multiple antibiotic resistance index of E. coli strains isolated from six drinking water sources during bacteriological monitoring over a year.…”
Section: Introductionmentioning
confidence: 99%
“…The common conditions for the growth of E. coli bacterium are stable temperature (>30 °C), relatively low pH, high humidity, and sufficient nutrients of carbon, nitrogen, and phosphorus . Generally, E. coli bacterium is cultured overnight in Luria–Bertani medium under soft shaking.…”
Section: Bacterium Organismsmentioning
confidence: 99%
“…Additionally, many FIB do not meet one of the central tenets of the concept: that they should mimic the fate of enteric pathogens in waterways. A number of studies have reported the persistence of FIB in extraintestinmal environments (Byappanahalli et al, 2012;Jang et al, 2017). Nevertheless, quantification of FIB is still applied to monitor the microbiological quality of recreational water worldwide.…”
Section: Culturable Fecal Indicator Bacteria and Alternativesmentioning
confidence: 99%
“…Due to their widespread occurrence and presumed relation to fecal pollution, E. coli and Enterococcus strains were initially thought to be good candidates for MST methods (Scott et al, 2002;Simpson et al, 2002). However, this has not proven to be the case, since their ubiquitous presence in feces and environmental persistence of these FIB rarely mimic that of pathogens (Byappanahalli et al, 2012;Jang et al, 2017;Staley et al, 2014). The primary idea underlying all MST approaches is that a specific trait of a bacterial group (e.g.…”
Section: Microbial Source Trackingmentioning
confidence: 99%